« We all have to fight for purity » : La production de discours sur la « pureté sexuelle » par de jeunes évangéliques américains sur YouTube (2017-2021) - Louise Chabanel-Gabriele (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
In the United States, while the heteronormative model of sexuality is being questioned in the public sphere, a group of conservative evangelicals has been developing a discourse on sexuality that sets “pure” sexuality apart from “impure” sexuality, heterosexual marriage being the only legitimate frame for “pure” sexuality. I offer to study the discourse of young evangelical YouTubers posted between 2017 and 2021, shedding light on the way the video and social network format allows for the preservation of conservative norms on a modern platform.